ENTREPRENEURIAL ELEMENTS IN RURAL TOURISM - FINDINGS FROM PLS-SEM - Ljiljana Šobić,; Bošković, Nikola; Danijela Pantović, (Economics of Agriculture, 2023)
The aim of this paper is to determine the interrelationship between innovation, proactivity and risk-taking, as a dimension of entrepreneurial orientation and their connection with relational capital, in order to indicate the entrepreneurial behavior that gives the best results for the development of sustainable rural tourism. The research was conducted on the basis of questionnaires collected on the territory of the Republic of Serbia during the year 2022. The data were analyzed using the PLS-SEM method. The results show a positive relationship between proactivity and innovation, between relational capital and innovation, and proactivity and relational capital, while a positive relationship between risktaking and innovation and risk-taking and relational capital was not confirmed. Results provide important elements for making decisions about innovation and competitiveness of rural tourism destinations.